Judging Time-to-Passage of looming sounds: evidence for the use of distance-based information - Silva, Rosa Mariana (2017)
Perceptual judgments are an essential mechanism for our everyday interaction with other moving agents or events. For instance, estimation of the time remaining before an object contacts or passes us is essential to act upon or to avoid that object. Previous studies have demonstrated that participants use different cues to estimate the time to contact or the time to passage of approaching visual stimuli. Despite the considerable number of studies on the judgment of approaching auditory stimuli, not much is known about the cues that guide listeners’ performance in an auditory Time-to-Passage (TTP) task. The present study evaluates how accurately participants judge approaching white-noise stimuli in a TTP task that included variable occlusion periods (portion of the presentation time where the stimulus is not audible). Results showed that participants were able to accurately estimate TTP and their performance, in general, was weakly affected by occlusion periods. Moreover, we looked into the psychoacoustic variables provided by the stimuli and analysed how binaural cues related with the performance obtained in the psychophysical task. The binaural temporal difference seems to be the psychoacoustic cue guiding participants’ performance for lower amounts of occlusion, while the binaural loudness difference seems to be the cue guiding performance for higher amounts of occlusion. These results allowed us to explain the perceptual strategies used by participants in a TTP task (maintaining accuracy by shifting the informative cue for TTP estimation), and to demonstrate that the psychoacoustic cue guiding listeners’ performance changes according to the occlusion period.